(untitled) (Annals of Medical Research, 2024)
Aim: This study aims to determine the prevalence of calcified atherosclerotic plaques (CAPs) incidentally encountered in the carotid artery within panoramic radiography (PR) images. Materials and Methods: A total of 1,200 patients (646 females, 554 males) referred to our clinic in January 2022 and January 2023 was included. CAPs within PRs were assessed, with data stratified by gender, age, and systemic conditions. Statistical analysis employed descriptive statistics and chi-square tests (p<0.05). Results: Among the 1200 patients, 251 CAPs (20.92%) were detected, with 128 (50.1%) occurring in females and 123 (49.9%) in males. The gender-based analysis demonstrated no statistically significant disparity in CAPs occurrence. Conversely, a notable correlation was established between the incidence of CAPs and age groups as well as systemic conditions (p<0.05). Conclusion: Panoramic radiography, routinely used in dental practice, offers a cost-effective, low-radiation means for preliminary CAPs assessment. Dental practitioners should consider referring patients with identified CAPs in PRs to cardiology departments, potentially reducing stroke risks.